O lugar do amar na relação ensino-aprendizagem da educação infantil e anos iniciais, contribuições de Humberto Maturana - Maciel, Jaqueline Goldschmidt (2023)
This research that I present as a Master's Dissertation in Education, in the line of research Training, Knowledge and Professional Development (PPGE - UFSM), entitled: The Place of Love in the Teaching-Learning Relationship of Early Childhood Education and Early Years, Contributions by Humberto Maturana, aims to: contribute with theoretical and epistemological subsidies for teaching activities in early childhood education and the initial years of elementary school, based on the propositions of cultural biology by Humberto Maturana. The references that guided this investigative and reflective look of the researcher were Valdo Barcelos, Humberto Maturana and Paulo Freire.It is noteworthy that we carried out a bibliographical research, based on the Biology of Love, conceiving education as a space of respect, love, cooperation, understanding that everything that happens to us is biological, but intermediated with our culture, in living and living together. The idea is that the reader understands that education starts from Loving, through coexistence, where the child has space to express and develop, being respected and welcomed in their differences. May our teachers understand that the school is a place of joy, of learning, collectivity, cooperation and never competition, a place of exchanging, of respect for oneself and the other, as a legitimate other, of enchantment, of mistakes and successes. Of LIFE, of affectionate, welcoming looks, of smiles, of hugs, where the school is a space of legitimacy, dialogue, acceptance, a place where the child in our hands is known, sensitizing them to the language of Love that we says Maturana and using the metaphor of the butterfly, I believe that all of us, beautiful butterflies, that one day as a caterpillar, breaks through the thickest layers to be the best of itself, we can break with what does not make sense to us and thus open space for let love be present. To live the present, because living is a gift.